State of the art on Energy Efficiency in Agriculture. Country data on energy consumption in different agro-production sectors in the European countries. - Golaszewski, J (2013)
Energy efficiency is the goal of efforts to reduce the amount of energy required to provide products and services. The general term "energy efficiency", when applied to agriculture,reflects changes in technology, governmental and EC policies – including the Common Agricultural Policy, climate change on a broad scale and local weather patterns, and farming management practices. There is not a single measure to describe, ensure, or improve energy efficiency. Instead, in the energy balance for a given production process, a variety of indicators may serve and support energy efficiency analysis. The results of this study are based on the specific input of primary energy per cultivation área (GJ ha-1) and on the specific input of primary energy per ton of agricultural product (GJ t-1). All the measures that are suitable to reduce the specific energy input, will improve energy efficiency (the energy efficiency measures). Improving energy efficiency of agricultural production contributes directly to the reduction of greenhouse gas (GHG) emissions, particularly carbon dioxide. This State of the Art analysis has been determined on the basis of the data provided by six countries: Finland, Germany, Greece, the Netherlands, Poland, and Portugal. The approach based on the life cycle analysis (LCA) has been chosen with the system boundary at the farm gate and have thus excluded processing into consumer goods. Specific energy input has been established for those agricultural products which have a decisive role in the EU foodstuff production, including: – crop production: wheat, sugar beet, potatoes, cotton, and sunflower; – greenhouse production of tomatoes, cucumber, and sweet pepper; – production of perennial crops such as vineyards and olive trees; – livestock production such as dairy cows (milk), pigs, and broilers. The analysis is based on average production figures, or best estimates, (should average figures be unavailable). In several cases figures have been found for different production systems within one country and up to three scenarios have been described. In this way, low, average, and high primary energy consumption (PEC) of the various production processes have been taken into consideration.